Radiation-proof electronic protective film

By using soft magnetic radiation-proof layer made of n-butyl titanate, ferrosilicon aluminum powder and modified ferrite in the electromagnetic shielding film, the shielding efficiency and high cost in the existing technology are solved. Problem, an electronic protective film with high magnetic permeability and electromagnetic shielding effect is suitable for industrial production and reduces the weight of the equipment.

CN119242138AInactive Publication Date: 2025-01-03ANHUI MINGXUN NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411764698.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing electromagnetic shielding films have insufficient shielding performance and high cost in the high frequency range. The use of nanometallic materials leads to large weight and are not suitable for lightweight equipment. The market's demand for broadband shielding has not been met.

Method used

Using a combination of double-sided adhesive and soft magnetic radiation-proof layer, the soft magnetic radiation-proof layer is made of n-butyl titanate, ferrosilicon aluminum powder and modified ferrite, and is coated with titanium dioxide. Methylammonium-based cage polysilsesquioxane is modified to form soft magnetic radiation-proof powder with high magnetic permeability and electromagnetic shielding effect, and is used together with modified ferrite to optimize the microstructure and electromagnetic characteristics of the material.

Benefits of technology

An electronic protective film with excellent magnetic permeability and electromagnetic shielding effect in the high-frequency electromagnetic range is realized, which reduces production costs, is suitable for industrial production, and improves the reliability and weather resistance of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242138A_ABST
    Figure CN119242138A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-radiation electronic protective film, and belongs to the field of preparation of electronic protective films. The electronic protective film comprises a double-sided adhesive tape and a soft magnetic radiation-proof layer on the double-sided adhesive tape, the soft magnetic anti-radiation layer is obtained by curing a soft magnetic anti-radiation coating; the soft magnetic anti-radiation coating comprises the following raw materials in parts by mass: 90-100 parts of epoxy resin, 35-70 parts of a solvent, 60-110 parts of a curing agent, 2-4 parts of a flame retardant and 3-6 parts of soft magnetic anti-radiation powder. The prepared electronic protective film is moderate in production cost, beneficial to industrial production, suitable for a high-frequency electromagnetic range and good in magnetic permeability and electromagnetic shielding effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a radiation-proof electronic protective film, and belongs to the field of electronic protective film preparation. Background Art

[0002] Electromagnetic interference (EMI) can have a series of adverse effects on electronic equipment and their systems, including: (1) Performance degradation: EMI can cause distortion of device signals and degradation of communication quality, affecting the normal performance of the equipment; (2) Safety hazards: In situations with high safety requirements, such as the aerospace field, EMI may cause serious accidents and serious consequences; (3) Failure and damage: Long-term exposure to severe EMI may cause equipment damage and early retirement; (4) Data loss: EMI may cause communication interruption and data loss, affecting the data integrity of the equipment; (5) System crash: EMI may cause system crash or freeze, resulting in data loss or failure to work properly; (6) Reduced reliability: EMI may reduce the reliability of electronic equipment and systems, shorten the life of the equipment, and increase the frequency of maintenance and replacement. Therefore, many studies are devoted to the development of electromagnetic shielding films that can effectively shield electromagnetic interference and protect electronic equipment from its effects.

[0003] Patent CN117183533A discloses a PET laminated card film and its preparation method, wherein the card film is composed of a PET base film layer, a shielding film layer on the upper surface of the PET base film layer, an electromagnetic shielding film layer on the upper surface of the shielding film layer, and a laminated adhesive layer on the lower surface of the PET base film layer; the shielding film layer is composed of a conductive material, a toughening agent, an epoxy resin, a silicone, and polyisocyanate; the electromagnetic shielding film layer is composed of a carbon conductive material, a metal absorbing material, and an epoxy resin. Although the invention can effectively shield electromagnetic influences through the synergistic shielding effect of the conductive material of the shielding film layer, the carbon conductive material and the metal absorbing material of the electromagnetic shielding film layer, and the nano-metal material of the PET base film layer; however, the raw materials in the invention, such as the nano-metal material composed of nano-silver and nano-copper, are expensive and have a high production cost, which is not conducive to further expanding the scope of production and application; and the weight is high, which is not suitable for equipment that needs to be lightweight. In addition, some electromagnetic shielding materials may have poor shielding effectiveness in the high-frequency range, and further research and improvement are needed to meet the market demand for broadband shielding.

[0004] With the popularization of electronic products and the development of wireless communication technology, the market demand for EMI electromagnetic shielding films will further increase. It is of practical significance to develop electronic protective films that can meet market demand and reduce electromagnetic interference between electronic devices. Summary of the invention

[0005] The invention discloses an anti-radiation electronic protective film. The electronic protective film of the invention has moderate production cost, is conducive to industrial production, is suitable for high-frequency electromagnetic range, and has good magnetic permeability and electromagnetic shielding effect.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The invention provides an anti-radiation electronic protective film, comprising a double-sided adhesive tape and a soft magnetic anti-radiation layer on the upper layer; the soft magnetic anti-radiation layer is obtained by curing a soft magnetic anti-radiation coating; the thickness of the soft magnetic anti-radiation layer is 100-300 μm, and the thickness of the double-sided adhesive tape is 10-50 μm.

[0007] In some embodiments, the soft magnetic radiation protection coating comprises the following raw materials in parts by mass: 90-100 parts of epoxy resin, 35-70 parts of solvent, 60-110 parts of curing agent, 2-4 parts of flame retardant, and 3-6 parts of soft magnetic radiation protection powder.

[0008] In some embodiments, the preparation steps of the soft magnetic radiation protection powder are: (1) Add n-butyl titanate to anhydrous ethanol, then add hydrochloric acid, stir for 30-60 minutes, then add sendust powder, stir and mix evenly, and dry to obtain solid powder 1; (2) dissolving the silicone resin in acetone, adding the solid powder 1 of step (1), stirring evenly, drying, cooling the obtained solid powder 2, mixing with zinc stearate, sieving, heating to 650-690°C in a nitrogen atmosphere at a heating rate of 7-9°C / min for 1-2h, cooling, soaking in the impregnation liquid mixture, washing, and drying to obtain solid powder 3; (3) The solid powder 3 of step (2) is placed in the modified mixed solution, mixed evenly, separated, and the solid part is heated at 80-90° C. for 2-3 h to obtain a soft magnetic radiation-proof powder.

[0009] In some embodiments, the mass ratio of n-butyl titanate to sendust powder is (0.85-2):100.

[0010] Preferably, the particle size of the Sendust powder is 1-50 μm.

[0011] Preferably, the mass ratio of n-butyl titanate to sendust powder is 1.5:100.

[0012] In some embodiments, the mass ratio of the silicone resin to the solid powder 1 is 1:(19-21), and the amount of zinc stearate used is 4.5-5wt% of the solid powder 2.

[0013] Preferably, the mass ratio of the silicone resin to the solid powder 1 is 1:20, and the amount of zinc stearate used is 4.75wt% of the solid powder 2.

[0014] In some embodiments, the ratio of the solid powder 3 to the modified mixed solution is 1 g: (1-1.2) mL; the modified mixed solution is a 1-3 wt % tetramethylammonium cage-shaped polysilsesquioxane-anhydrous ethanol solution.

[0015] Preferably, the ratio of the solid powder 3 to the modified mixed solution is 1 g:1.1 mL; the modified mixed solution is a 1.8 wt % tetramethylammonium cage-shaped polysilsesquioxane-anhydrous ethanol solution.

[0016] In some embodiments, the soft magnetic radiation protection coating further comprises 1-5 parts by mass of modified ferrite; the preparation steps of the modified ferrite are: The graphene oxide is dispersed in a polyethylene glycol aqueous solution with a concentration of 10-12wt%, and ultrasonically treated to obtain a graphene oxide dispersion, to which barium nitrate, iron nitrate and praseodymium nitrate are added, and stirred for 1-2h, and the pH of the solution is adjusted to 6.5-7.5, and stirred again to obtain a coprecipitation precursor solution, and the coprecipitation precursor solution is reacted in a reactor at 210-250°C for 6-8h, naturally cooled to room temperature, washed, dried, and ground to obtain a modified ferrite.

[0017] In some embodiments, the molar ratio of barium nitrate, iron nitrate and praseodymium nitrate is 1:(7-9):(1.1-2.3).

[0018] Preferably, the molar ratio of barium nitrate, iron nitrate and praseodymium nitrate is 1:8.5:1.8.

[0019] In some embodiments, the amount of graphene oxide used is 50-80% of the total mass of barium nitrate, iron nitrate and praseodymium nitrate; the thickness of the graphene oxide is ≤5 nm and the sheet diameter is 1-10 μm.

[0020] Preferably, the amount of graphene oxide used is 60% of the total mass of barium nitrate, iron nitrate and praseodymium nitrate.

[0021] In some embodiments, the epoxy equivalent of the epoxy resin is 150-200 g / eq.

[0022] The electronic protection film obtained in the present invention has an operating temperature of -40 to 120° C. and an operating frequency of ≤10 GHz.

[0023] The present invention coats the sendust powder with titanium dioxide, and then modifies it with tetramethylammonium cage-shaped polysilsesquioxane to obtain a soft magnetic radiation-proof powder with high magnetic permeability and electromagnetic shielding effect. The present invention uses n-butyl titanate hydrolysis to prepare the sendust magnetic powder with surface insulation coating, realizes the simultaneous surface coating and magnetic powder flake formation, and simplifies the process flow. The chemical bonds of titanium dioxide are connected to the surface of the sendust flaky magnetic powder, making the coating tighter, effectively enhancing the insulation effect, and further improving the wave absorption performance and insulation effect of the sendust magnetic powder through high-temperature calcination treatment. In addition, by coating with a titanium dioxide insulating layer, the resistivity of the powder can be increased, and the eddy current loss generated by the sendust at high frequencies can be reduced. At the same time, the insulating layer enhances the impedance matching of the sendust powder, making it a good wave absorber. Finally, the present invention utilizes the tetramethylammonium group of tetramethylammonium cage-shaped polysilsesquioxane to react with the surface of the sendust powder, which may enhance the surface polarity of the powder, thereby improving the binding force with the TiO2 coating layer and promoting the formation of a more uniform and dense TiO2 coating layer, which helps to improve the electromagnetic shielding effect of the material. The tetramethylammonium cage-shaped polysilsesquioxane modification may also produce a synergistic effect with the titanium dioxide coating layer, further improving its electromagnetic shielding performance by optimizing the microstructure and electromagnetic properties of the material.

[0024] The present invention also prepares modified ferrite by co-precipitation of graphene oxide with barium nitrate, iron nitrate and praseodymium nitrate in a specific molar ratio. By controlling precipitation conditions (such as pH value, temperature, reaction time, etc.), the particle size, morphology and phase composition of the product can be adjusted, thereby obtaining a modified ferrite material with specific properties, which can well enhance the magnetic properties. Iron nitrate and praseodymium nitrate are common raw materials for ferrite magnetic materials. Their mixture can form ferrite with specific magnetic properties, and the addition of graphene oxide may enhance the magnetism of ferrite through interface effects, further improve the conductivity, dispersibility and chemical stability, which may be due to the fact that the conductive properties of graphene oxide can improve the conductivity of the composite material, and its large specific surface area and surface activity also help to improve the dispersibility of ferrite nanoparticles in the matrix, thereby obtaining a more uniform microstructure, and enhancing the mechanical properties of ferrite by forming a composite material, and improving the hardness and wear resistance of the material. In addition, the present invention optimizes the electromagnetic properties by adjusting the ratio of barium nitrate, iron nitrate and praseodymium nitrate. During the co-precipitation process, graphene oxide can also serve as a template to promote the formation of a core-shell structure on the surface of ferrite particles, which is more helpful to improve the magnetic properties and shielding effectiveness of the material.

[0025] Based on the problems existing in the prior art, the beneficial effects of the present invention are:

[0026] 1. The present invention provides an electronic protective film, which uses soft magnetic radiation protection powder and modified ferrite together to obtain a soft magnetic radiation protection layer, and then prepares an electronic protective film suitable for high-frequency electromagnetic range, which has excellent magnetic permeability and electromagnetic shielding effect.

[0027] 2. The present invention coats sendust powder with titanium dioxide, and then modifies it with tetramethylammonium cage-shaped polysilsesquioxane to optimize the microstructure and electromagnetic properties of the material, thereby obtaining a soft magnetic radiation-proof powder with high magnetic permeability and electromagnetic shielding effect.

[0028] 3. The present invention prepares modified ferrite by co-precipitation of graphene oxide with barium nitrate, ferric nitrate and praseodymium nitrate in a specific molar ratio, and adjusts the particle size, morphology and phase composition of the product by controlling the precipitation conditions, thereby obtaining a modified ferrite material with specific properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Actual picture of electronic protective film for radiation protection. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. Various modifications and variations may be made to the specific embodiments of the present invention specification without departing from the scope or spirit of the present invention, which will be apparent to those skilled in the art. Other embodiments obtained from the present invention specification will be apparent to the technician. The present application specification and examples are exemplary only.

[0033] The words “include,” “including,” “have,” or “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] The mass fractions described in the following embodiments may be grams, kilograms, tons or other mass units.

[0035] The sendust powder used in the present invention is a 300-mesh spherical soft magnetic powder purchased from Shandong Xinbaiyi Metal Materials Co., Ltd.; the silicone resin used is MQ silicone resin purchased from MESON Silicone; the zinc stearate used is 325 mesh; the polyethylene glycol used is polyethylene glycol 600; the graphene oxide used is graphene oxide purchased from Xianfeng Nano with item number 100003; the impregnation liquid used is purchased from Kenmet Materials Technology Co., Ltd.; the epoxy resin used is epoxy resin purchased from DIC with item number HP-4710; the curing agent used is methyltetrahydrophthalic anhydride; and the flame retardant used is tributyl phosphate.

[0036] Preparation Example 1 The preparation steps of soft magnetic radiation protection powder are as follows: (1) Add 1.5 g of n-butyl titanate to 25 mL of anhydrous ethanol, then add 0.04 mL of AR grade hydrochloric acid, stir for 50 min, then add 100 g of sendustine powder, stir and mix evenly, and dry at 60°C to constant weight to obtain solid powder 1; (2) Dissolve 1 g of silicone resin in 3 mL of acetone, add 100 g of the solid powder 1 of step (1), stir evenly, and dry at 60° C. to constant weight. Cool 100 g of the obtained solid powder 2, mix evenly with 1 g of zinc stearate, pass through a 100-mesh sieve, heat to 670° C. in a nitrogen atmosphere at a heating rate of 8° C. / min, and keep warm for 1.5 h. After cooling to room temperature, soak in 200 mL of the impregnation liquid mixture (the mass ratio of the impregnation liquid to tetrachloroethylene is 1:2) for 15 min, wash with tetrachloroethylene 3 times, and dry at 60° C. to constant weight to obtain solid powder 3; (3) 100 g of the solid powder 3 of step (2) was placed in 110 mL of the modified mixed solution, stirred at 100 r / min for 15 min, and then centrifuged. The solid part was heated at 85° C. for 2.5 h to obtain a soft magnetic radiation-proof powder.

[0037] The modified mixed solution used is a 1.8 wt % tetramethylammonium cage-shaped polysilsesquioxane-anhydrous ethanol solution.

[0038] Preparation Example 2 The preparation steps of soft magnetic radiation protection powder are as follows: (1) Add 1.5 g of n-butyl titanate to 25 mL of anhydrous ethanol, then add 0.04 mL of AR grade hydrochloric acid, stir for 50 min, then add 100 g of sendustine powder, stir and mix evenly, and dry at 60°C to constant weight to obtain solid powder 1; (2) Dissolve 1 g of silicone resin in 3 mL of acetone, add 100 g of the solid powder 1 of step (1), stir evenly, and dry at 60 ° C to constant weight. After cooling, mix 100 g of the obtained solid powder 2 evenly with 1 g of zinc stearate, pass through a 100-mesh sieve, heat to 670 ° C in a nitrogen atmosphere at a heating rate of 8 ° C / min, and keep warm for 1.5 h. After cooling to room temperature, soak in 200 mL of impregnation liquid mixture (the mass ratio of impregnation liquid to tetrachloroethylene is 1:2) for 15 min, wash with tetrachloroethylene 3 times, and dry at 60 ° C to constant weight to obtain soft magnetic radiation protection powder.

[0039] Preparation Example 3 The preparation steps of soft magnetic radiation protection powder are as follows: (1) Dissolve 1 g of silicone resin in 3 mL of acetone, add 100 g of iron-silicon-aluminum powder, stir evenly, and dry at 60 ° C to constant weight. After cooling, mix 100 g of the obtained solid powder 1 evenly with 1 g of zinc stearate, pass through a 100-mesh sieve, heat to 670 ° C in a nitrogen atmosphere at a heating rate of 8 ° C / min, and keep warm for 1.5 h. After cooling to room temperature, soak in 200 mL of impregnation liquid mixture (the mass ratio of impregnation liquid to tetrachloroethylene is 1:2) for 15 min, wash with tetrachloroethylene 3 times, and dry at 60 ° C to constant weight to obtain solid powder 2; (2) 100 g of the solid powder 2 obtained in step (2) was placed in 110 mL of the modified mixed solution, stirred at 100 r / min for 15 min, and then centrifuged. The solid part was heated at 85° C. for 2.5 h to obtain a soft magnetic radiation-proof powder.

[0040] The modified mixed solution used is a 1.8 wt % tetramethylammonium cage-shaped polysilsesquioxane-anhydrous ethanol solution.

[0041] Preparation Example 4 The preparation steps of the soft magnetic radiation-proof powder are the same as those in Preparation Example 1, except that 0.5 g of n-butyl titanate is used.

[0042] Preparation Example 5 The preparation steps of the soft magnetic radiation-proof powder are the same as those in Preparation Example 1, except that 2.2 g of n-butyl titanate is used.

[0043] Preparation Example 6 The preparation steps of modified ferrite are: 12 g of graphene oxide was dispersed in 100 mL of 11 wt % polyethylene glycol aqueous solution, and ultrasonically treated at 20 KHz for 15 min to obtain a graphene oxide dispersion, to which 20 g of barium nitrate, iron nitrate and praseodymium nitrate in a molar ratio of 1:8.5:1.8 were added, stirred at 100 r / min for 1.5 h, the pH of the solution was adjusted to 7, and stirred for another 1 h to obtain a coprecipitation precursor solution, the coprecipitation precursor solution was reacted in a reactor at 235 ° C for 7 h, naturally cooled to room temperature, the precipitate was washed 3 times with deionized water and anhydrous ethanol respectively, dried at 60 ° C to constant weight, and ground to 1 μm to obtain a modified ferrite.

[0044] Preparation Example 7 The preparation steps of the modified ferrite are the same as those of Preparation Example 6, except that the reaction temperature is 260°C.

[0045] Preparation Example 8 The preparation steps of modified ferrite are: To 100 mL of 10-12 wt % polyethylene glycol aqueous solution, add 20 g of barium nitrate, iron nitrate and praseodymium nitrate in a molar ratio of 1:8.5:1.8, stir at 100 r / min for 1.5 h, adjust the solution pH to 7, and stir for another 1 h to obtain a coprecipitation precursor solution. The coprecipitation precursor solution was reacted in a reactor at 235 ° C for 7 h, naturally cooled to room temperature, and the precipitate was washed 3 times with deionized water and anhydrous ethanol, dried at 60 ° C to constant weight, and ground to 1 μm to obtain modified ferrite.

[0046] Preparation Example 9 The preparation steps of the modified ferrite are the same as those of Preparation Example 6, except that the molar ratio of barium nitrate, iron nitrate and praseodymium nitrate used is 1:6.5:1.8.

[0047] Preparation Example 10 The preparation steps of the modified ferrite are the same as those in Preparation Example 6, except that 9 g of graphene oxide is used.

[0048] Example 1 A radiation-proof electronic protective film comprises a PET acrylic double-sided adhesive tape and a soft magnetic radiation-proof layer on the upper layer; the soft magnetic radiation-proof layer is obtained by curing a soft magnetic radiation-proof coating; the thickness of the soft magnetic radiation-proof layer is 200 μm, and the thickness of the PET acrylic double-sided adhesive tape is 30 μm.

[0049] The soft magnetic radiation-proof coating comprises the following raw materials, calculated by weight: 95 parts of epoxy resin, 50 parts of cyclohexane, 100 parts of curing agent, 3 parts of flame retardant, and 4.5 parts of soft magnetic radiation-proof powder.

[0050] The soft magnetic radiation-proof powder used is obtained from Preparation Example 1.

[0051] Example 2 A radiation-proof electronic protective film, the specific implementation method is the same as that of Example 1, except that the soft magnetic radiation-proof powder used is obtained from Preparation Example 2.

[0052] Example 3 A radiation-proof electronic protective film, the specific implementation method is the same as that of Example 1, except that the soft magnetic radiation-proof powder used is obtained from Preparation Example 3.

[0053] Example 4 A radiation-proof electronic protective film, the specific implementation method is the same as that of Example 1, except that the soft magnetic radiation-proof powder used is obtained from Preparation Example 4.

[0054] Example 5 A radiation-proof electronic protective film, the specific implementation method is the same as that of Example 1, except that the soft magnetic radiation-proof powder used is obtained from Preparation Example 5.

[0055] Example 6 A radiation-proof electronic protective film comprises a PET acrylic double-sided adhesive tape and a soft magnetic radiation-proof layer on the upper layer; the soft magnetic radiation-proof layer is obtained by curing a soft magnetic radiation-proof coating; the thickness of the soft magnetic radiation-proof layer is 200 μm, and the thickness of the PET acrylic double-sided adhesive tape is 30 μm.

[0056] The soft magnetic radiation-proof coating comprises the following raw materials, calculated by weight: 95 parts of epoxy resin, 50 parts of cyclohexane, 100 parts of curing agent, 3 parts of flame retardant, 4.5 parts of soft magnetic radiation-proof powder, and 3 parts of modified ferrite.

[0057] The soft magnetic radiation protection powder used is obtained from Preparation Example 1, and the modified ferrite used is obtained from Preparation Example 6.

[0058] Example 7 A radiation-proof electronic protective film, the specific implementation method is the same as Example 6, the difference is that the modified ferrite used is obtained from Preparation Example 7.

[0059] Example 8 A radiation-proof electronic protective film, the specific implementation method is the same as Example 6, the difference is that the modified ferrite used is obtained from Preparation Example 8.

[0060] Example 9 A radiation-proof electronic protective film, the specific implementation method is the same as Example 6, the difference is that the modified ferrite used is obtained from Preparation Example 9.

[0061] Example 10 A radiation-proof electronic protective film, the specific implementation method is the same as Example 6, the difference is that the modified ferrite used is obtained from Preparation Example 10.

[0062] Embodiment 11 A radiation-proof electronic protective film, the specific implementation method is the same as that of Example 1, except that an equal mass of sendust powder is used instead of the soft magnetic radiation-proof powder.

[0063] Example 12 A radiation-proof electronic protective film comprises a PET acrylic double-sided adhesive tape and a soft magnetic radiation-proof layer on the upper layer; the soft magnetic radiation-proof layer is obtained by curing a soft magnetic radiation-proof coating; the thickness of the soft magnetic radiation-proof layer is 100 μm, and the thickness of the PET acrylic double-sided adhesive tape is 10 μm.

[0064] The soft magnetic radiation-proof coating comprises the following raw materials, calculated by weight: 90 parts of epoxy resin, 35 parts of cyclohexane, 60 parts of curing agent, 2 parts of flame retardant, and 3 parts of soft magnetic radiation-proof powder.

[0065] The soft magnetic radiation-proof powder used is obtained from Preparation Example 1.

[0066] Embodiment 13 A radiation-proof electronic protective film comprises a PET acrylic double-sided adhesive tape and a soft magnetic radiation-proof layer on the upper layer; the soft magnetic radiation-proof layer is obtained by curing a soft magnetic radiation-proof coating; the thickness of the soft magnetic radiation-proof layer is 300 μm, and the thickness of the PET acrylic double-sided adhesive tape is 50 μm.

[0067] The soft magnetic radiation-proof coating comprises the following raw materials, measured by weight: 100 parts of epoxy resin, 70 parts of cyclohexane, 110 parts of curing agent, 4 parts of flame retardant, and 6 parts of soft magnetic radiation-proof powder.

[0068] The soft magnetic radiation-proof powder used is obtained from Preparation Example 1.

[0069] Performance test of electronic protective film The following performance tests were performed on each embodiment:

[0070] 1. Adhesion test method: Test according to ASTM D3359-09 standard, and measure the coating adhesion performance / plating adhesion by tape.

[0071] 2. Electromagnetic shielding effectiveness test method: Test in accordance with GB / T30142-2013 standard.

[0072] 3. Density: Tested in accordance with ASTM D792 standard.

[0073] 4. Magnetic permeability: Use eysight E499B impedance analyzer for testing.

[0074] 5. Weather resistance: Test the magnetic permeability after placing it under high temperature and high humidity (90℃ / 85%RH) for 120 hours.

[0075] The specific test results are shown in Table 1.

[0076] Table 1

[0077] As can be seen from Table 1, the electronic protection films prepared in Examples 1, 12, and 13 have good weather resistance, and good electromagnetic shielding effectiveness and magnetic permeability. In Example 6, due to the addition of modified ferrite, its comprehensive performance such as electromagnetic shielding effectiveness and magnetic permeability is further improved. Compared with Example 1, the preparation process of the soft magnetic radiation protection powder used in Examples 2-5 has changed (tetramethylammonium cage-shaped polysilsesquioxane modification is not used, n-butyl titanate is not used for coating, and the amount of n-butyl titanate is changed), and in Example 11, iron silicon aluminum powder is used instead of soft magnetic radiation protection powder, which will cause the electromagnetic shielding effectiveness and magnetic permeability of the electronic protection film to decrease. Compared with Example 6, the preparation process of the modified ferrite used in Examples 7-8 was changed (reaction temperature, no addition of graphene oxide, molar ratio of raw materials, improper amount of graphene oxide), which changed the internal structure of the modified ferrite, affecting its own performance, thereby resulting in varying degrees of reduction in the electromagnetic shielding effectiveness and comprehensive magnetic permeability performance of the soft magnetic anti-radiation layer on the electronic protective film.

[0078] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.

Claims

1. A radiation-proof electronic protective film, characterized in that: It comprises a double-sided adhesive tape and a soft magnetic radiation-proof layer on the upper layer; the soft magnetic radiation-proof layer is obtained by curing a soft magnetic radiation-proof coating; the thickness of the soft magnetic radiation-proof layer is 100-300 μm, and the thickness of the double-sided adhesive tape is 10-50 μm; The soft magnetic radiation-proof coating comprises the following raw materials, calculated by weight: 90-100 parts of epoxy resin, 35-70 parts of cyclohexane, 60-110 parts of curing agent, 2-4 parts of flame retardant, and 3-6 parts of soft magnetic radiation-proof powder; The preparation steps of the soft magnetic radiation-proof powder are as follows: (1) Add n-butyl titanate to anhydrous ethanol, then add hydrochloric acid, stir for 30-60 minutes, then add sendust powder, stir and mix evenly, and dry to obtain solid powder 1; (2) dissolving the silicone resin in acetone, adding the solid powder 1 of step (1), stirring evenly, drying, cooling the obtained solid powder 2, mixing with zinc stearate, sieving, heating to 650-690°C in a nitrogen atmosphere at a heating rate of 7-9°C / min for 1-2h, cooling, soaking in the impregnation liquid mixture, washing, and drying to obtain solid powder 3; (3) The solid powder 3 of step (2) is placed in the modified mixed solution, mixed evenly, separated, and the solid part is heated at 80-90° C. for 2-3 h to obtain a soft magnetic radiation-proof powder.

2. The radiation-proof electronic protective film according to claim 1, characterized in that: The mass ratio of n-butyl titanate to sendust powder is (0.85-2):

100.

3. The radiation-proof electronic protective film according to claim 1, characterized in that: The mass ratio of the silicone resin to the solid powder 1 is 1:(19-21), and the amount of zinc stearate used is 4.5-5wt% of the solid powder 2.

4. The radiation-proof electronic protective film according to claim 1, characterized in that: The ratio of the solid powder 3 to the modified mixed solution is 1 g: (1-1.2) mL; the modified mixed solution is a 1-3 wt % tetramethylammonium cage-shaped polysilsesquioxane-anhydrous ethanol solution.

5. The radiation-proof electronic protective film according to claim 1, characterized in that: The soft magnetic radiation protection coating further comprises 1-5 parts by mass of modified ferrite, and the preparation steps of the modified ferrite are as follows: The graphene oxide is dispersed in a polyethylene glycol aqueous solution with a concentration of 10-12wt%, and ultrasonically treated to obtain a graphene oxide dispersion liquid, to which barium nitrate, iron nitrate and praseodymium nitrate are added, and stirred for 1-2h, and the pH value of the solution is adjusted to 6.5-7.5, and stirred again to obtain a coprecipitation precursor solution, and the coprecipitation precursor solution is reacted in a reactor at 210-250°C for 6-8h, naturally cooled to room temperature, washed, dried, and ground to obtain a modified ferrite.

6. The radiation-proof electronic protective film according to claim 5, characterized in that: The molar ratio of the barium nitrate, the iron nitrate and the praseodymium nitrate is 1:(7-9):(1.1-2.3).

7. The radiation-proof electronic protective film according to claim 5, characterized in that: The usage amount of the graphene oxide is 50-80% of the total mass of barium nitrate, iron nitrate and praseodymium nitrate; the thickness of the graphene oxide is ≤5 nm and the sheet diameter is 1-10 μm.

8. The radiation-proof electronic protective film according to claim 1, characterized in that: The epoxy equivalent of the epoxy resin is 150-200 g / eq.

Citation Information

Patent Citations

  • PET laminated card film and preparation method thereof

    CN117183533A